2010
DOI: 10.1063/1.3527994
|View full text |Cite
|
Sign up to set email alerts
|

Stellarator coil design and plasma sensitivity

Abstract: The rich information contained in the plasma response to external magnetic perturbations can be used to help design stellarator coils more effectively. We demonstrate the feasibility by first developing a simple, direct method to study perturbations in stellarators that do not break stellarator symmetry and periodicity. The method applies a small perturbation to the plasma boundary and evaluates the resulting perturbed free-boundary equilibrium to build up a sensitivity matrix for the important physics attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…2007, 2008), figure 2. Boozer and Ku studied the sensitivity of stellarator neoclassical transport (Ku & Boozer 2010 b ; Boozer & Ku 2011), figure 3. In both studies, the plasma sensitivity was found to drop essentially exponentially.…”
Section: Coilsmentioning
confidence: 99%
See 1 more Smart Citation
“…2007, 2008), figure 2. Boozer and Ku studied the sensitivity of stellarator neoclassical transport (Ku & Boozer 2010 b ; Boozer & Ku 2011), figure 3. In both studies, the plasma sensitivity was found to drop essentially exponentially.…”
Section: Coilsmentioning
confidence: 99%
“…Park studied the sensitivity of tokamaks to perturbations that drive magnetic islands (Park et al 2007(Park et al , 2008, figure 2. Boozer and Ku studied the sensitivity of stellarator neoclassical transport (Ku & Boozer 2010b;Boozer & Ku 2011), figure 3. In both studies, the plasma sensitivity was found to drop essentially exponentially.…”
Section: Plasma Optimization and Sensitivitymentioning
confidence: 99%
“…Generally, lower f B implies lower residual normal field on the surface, and a coil set which more accurately reproduces the desired plasma shape. Although it's proven that the plasma doesn't have the same sensitivity to all external magnetic perturbations [18], we can easily modify the evaluation function by replacing f B with a suitably weighted summation as m,n w m,n B n m,n in the future. The first and second derivatives of f B with respect to all the coil parameters in X, namely the gradient g and the Hessian H, can be calculated analytically in FOCUS.…”
Section: Brief Overview Of Focusmentioning
confidence: 99%
“…In addition to concept investigations, plasma studies were carried out looking at aspect-ratio scans for improvements on magnet complexity and computational searches to identify attractive quasi-symmetric configurations [25][26].…”
Section: Csmentioning
confidence: 99%